Antioxidant and antibacterial activities of different solvent extractions from Cassia siamea (Lamk.) leaves - Phaiphan, Anuthida; Baharin, Badlishah Sham; Tan, Chin Ping; Abdul Rahman, Russly; Ganesan, Palanivel (Journal of Chemical and Pharmaceutical Research, 2014)
The objective of this study was to determine the yield, total phenolic content (TPC), antioxidant and antibacterial activities of the extract from C. siamea leaves by using different solvent extractions. The antibacterial potential was tested by disc diffusion method against seven strains of bacteria, Staphylococcus sp. BCC 5357, Bacillus cereus ATCC 33019,Vibrio parahaemolyticus ATCC 17802, Escherichia coli ATCC 25922, Salmonella typhimurium ATCC 14028, Salmonella enteritidis ATCC 13076 and Pseudomonas aeruginosa BCC 30506.Methanol extractions showed a significantly higher yield, TPC, antioxidant and antibacterial activity than other solvents (p<0.05). The zone of inhibition of the extracts ranged from 6.30 to 9.30 mm irrespective of the solvents used in the extractions. Gram positive bacteria showed significantly higher inhibition than gran-negative bacteria. This study confirmed that various solvent extractions of C. siamea leaves showed antioxidant and antibacterial activities against various microbes.